EVALUASI SISTEM PENGENDALIAN INTERNAL ATAS PROSEDUR PENERIMAAN PENDAPATAN TRANSAKSI TOL NONTUNAI (E-TOLL) PADA PT JASA MARGA (PERSERO) TBK. CABANG PURBALEUNYI - Siti Devi; Khozin Arief; Setiawan Setiawan (Ma'soem University, 2019)
PT Jasa Marga (Persero) Tbk. Purbaleunyi Branch is a state-owned enterprise service, as enforcement and services for the toll road. In providing services that are effective, efficient, safe, comfortable, and ease the accessibility of toll roads for users, a non-cash toll payment system is implemented (e-toll). The implementation of internal control at PT Jasa Marga (Persero) Tbk. Purbaleunyi Branch still has weaknesses, such as the placement of employees are placed unsuitable with their education and proficiency causing inefficient work. Moreover, there is no written policy on standard operating procedures regarding receipt of e-toll income and job rotation that are not routinely do so that the vulnerability of fraud occurs. This study aims to evaluate the implementation of internal control on the non-cash receipt of toll transaction procedure (e-toll) that applied by PT Jasa Marga (Persero) Tbk. Purbaleunyi Branch. The method used in this research is descriptive analytics method by taking interviews, observation, and documentation. The analytics tool used in this study is a control matrix based on the Committee of Sponsoring Organizations.Based on the results of this research, it can be concluded that internal control on the non-cash receipt of toll transaction procedure (e-toll) at PT Jasa Marga (Persero) Tbk. Purbaleunyi Branch has been adequate and effective.